2021
DOI: 10.3390/brainsci11020269
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse Inhibition in Cocaine Addiction and Dual Pathologies

Abstract: Cocaine addiction is frequently associated with different psychiatric disorders, especially schizophrenia and antisocial personality disorder. A small number of studies have used prepulse inhibition (PPI) as a discriminating factor between these disorders. This work evaluated PPI and the phenotype of patients with cocaine-related disorder (CRD) who presented a dual diagnosis of schizophrenia or antisocial personality disorder. A total of 74 men aged 18–60 years were recruited for this research. The sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Regarding PPI in patients using cannabis, all reviewed studies observed lower prepulse inhibition than subjects in the control group [ 137 139 , 141 , 142 ]. Conversely, in studies evaluating patients using cocaine, a generally higher PPI was found among patients compared to controls [ 134 , 140 , 143 , 144 ]. Similarly, one of the reviewed studies analyzing ecstasy found the same trend [ 135 ] while another did not find any differences [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding PPI in patients using cannabis, all reviewed studies observed lower prepulse inhibition than subjects in the control group [ 137 139 , 141 , 142 ]. Conversely, in studies evaluating patients using cocaine, a generally higher PPI was found among patients compared to controls [ 134 , 140 , 143 , 144 ]. Similarly, one of the reviewed studies analyzing ecstasy found the same trend [ 135 ] while another did not find any differences [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…These areas had previously been related to PPI in both animals and humans [ 41 , 44 46 ]. Additionally, changes in neurotransmission such as hyperactivation of the dopaminergic system [ 95 , 83 , 115 , 134 , 142 , 143 ] and dysfunction of the glutamatergic, GABAergic, and catecholaminergic systems have also been associated with PPI disruption [ 84 , 89 , 90 , 135 , 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BIS‐11 contains 30‐items grouped into three subscales: attentional (intolerance of complexity), motor (impetuous action), and nonplanning (lack of future orientation) impulsiveness. The BIS has previously been used to assess impulsiveness in patients with schizophrenia (e.g., Fuertes‐Saiz et al, 2019; Gil‐Miravet et al, 2021). The present study revealed a Cronbach's alpha coefficient of 0.896 for the total BIS‐11.…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 26 to 104. The LSRPS psychopathy has been used by previous researchers to investigate psychopathy traits among patients with schizophrenia (e.g., Fuertes‐Saiz et al, 2019; Gil‐Miravet et al, 2021). For the current sample, the reliability of the LSRPS total score was good (Cronbach's alpha = 0.746).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation